The Effect of Economic Conditions on the Success of Equal Employment Opportunity Laws: An Application to the Sex Differential in Earnings - Beller, Andrea H. (The Review of Economics and Statistics, 1980)
Andrea H. Beller, The Effect of Economic Conditions on the Success of Equal Employment Opportunity Laws: An Application to the Sex Differential in Earnings, The Review of Economics and Statistics, Vol. 62, No. 3 (Aug., 1980), pp. 379-387